PEMBATALAN PENETAPAN STATUS TERSANGKA DALAM PERKARA DUGAAN TINDAK PIDANA KORUPSI (STUDI PUTUSAN PRAPERADILAN NOMOR 1/Pid.Prap/2021/PN KSN): Cancellation of The Determination of Suspect Status in A Case of Alleged Corruption (Study of Petrial Decision Number 1/Pid.Prap/2021/PN Ksn) - Muhammad Fauzan Ridho Kanungga Rominton; Setiyono (Faculty of Law, Universitas Trisakti, 2025)
In recent years, many corruption cases have had their suspect status revoked by the Pretrial Judge due to insufficient evidence. This study aims to provide an overview and analysis of the revocation of the determination of suspect status in alleged corruption cases by the Kasongan District Court with Number 1/Pid Prap/2021/PN Ksn. The main focus of the law discussed is whether the determination of suspect status by the Investigator has been based on the requirements in the Criminal Procedure Code (KUHAP), and whether the legal considerations and dictum of the Kasongan District Court Pretrial Judge’s decision stating the invalidity of the determination of suspect status are in accordance with the applicable laws and regulations. The results of the study indicate that the determination of suspect status by the Investigator is based on the requirements stipulated in Articles 16–19 of the Criminal Procedure Code, and the considerations of the Judge’s decision stating the invalidity of the determination of suspect status are in accordance with the applicable laws and regulations based on the juridical aspect, that there are not at least 2 sufficient preliminary evidence as stipulated in Article 184 of the Criminal Procedure Code. This study concludes that both the Investigator’s determination and the Judge’s decision were based on existing legal requirements and provisions, despite some disagreement. This study recommends that regulatory agencies be more detailed in creating and formulating legal regulations to avoid multiple interpretations.